Socialization and Optimization of Financial Record-Keeping through the Utilization of JURNAL ID at PT Swabina Gatra Travel: Sosialisasi dan Optimalisasi Pencatatan Keuangan Melalui Pemanfaatan JURNAL ID pada PT Swabina Gatra Travel - Fellisha Arianti; Daisy Marthina Rosyanti (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
This Community Service Program aimed to improve the efficiency and accuracy of financial record management at PT Swabina Gatra Travel through the optimization of the digital accounting system, Jurnal.id. The main challenges identified included limited automation of administrative fees, restricted flexibility in transaction item arrangement, and a high reliance on manual input, which increased the risk of recording errors and invoice returns. The intervention was implemented through technical training, the development of transaction flowcharts, and the establishment of a structured Standard Operating Procedure (SOP) as an operational guideline. Post-implementation evaluation demonstrated significant performance improvements. System usage efficiency increased by 24.2%, feature suitability with operational needs improved by 25.7%, accuracy and error control rose by 28.6%, and user independence and competence increased by 31.4%. These findings indicate that structured technical assistance and procedural standardization effectively reduced input errors, accelerated administrative processes, and strengthened financial governance. Overall, the intervention successfully enhanced financial recording performance while reinforcing employee competence and organizational readiness for sustainable and transparent digital transformation.